The Influence of Job Performance on Promotion - Kristiansen, Stein; Yusuf, Muhammad (Yayasan Pendidikan Belajar Berdikari, 2023)
This study took a survey approach, including quantitative research methods. This study's population and sample size were 26 employees. Questionnaires and interviews were used to collect data. In this work, data analysis approaches such as partial least squares (PLS) and hypothesis testing were applied. In this study, data is processed using software called Smart PLS 4.0. According to the study's findings, the first hypothesis test revealed a correlation value of 0.262 between job experience and promotion. The findings of the second hypothesis test demonstrate that the correlation between job performance factors and promotion is 0.005. According to the calculations, job experience has no significant effect on promotion, however work performance has a considerable effect on promotion